2017
DOI: 10.1111/mcn.12431
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary patterns during pregnancy and intelligence quotients in the offspring at 8 years of age: Findings from the ALSPAC cohort

Abstract: Dietary intake during pregnancy may influence child neurodevelopment and cognitive function. This study aims to investigate the associations between dietary patterns obtained in pregnancy and intelligence quotients (IQ) among offspring at 8 years of age. Pregnant women enrolled in the Avon Longitudinal Study of Parents and Children completed a food frequency questionnaire at 32 weeks' gestation (n = 12,195). Dietary patterns were obtained by cluster analysis. Three clusters best described women's diets during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Among 23,020 children in the Norwegian Mother and Child Cohort Study, Jacka et al (2013) reported that “unhealthy” maternal diet patterns during pregnancy were associated with increased externalizing child behaviors. A recent study in the United Kingdom suggested that maternal diets characterized by higher intakes of fruits and vegetables and lower intakes of meat and potatoes are associated with higher child IQ at age 8 years ( Freitas-Vilela et al, 2017 ). In the Generation R study involving 3,104 children, investigators reported decreased levels of externalizing behaviors from children born to mothers who adhered to a Mediterranean diet during pregnancy, and increased child externalizing behaviors in children born to mothers who consumed a “Traditionally Dutch” diet consisting of high meat intake (processed and unprocessed), margarines and potatoes ( Steenweg-de Graaff et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among 23,020 children in the Norwegian Mother and Child Cohort Study, Jacka et al (2013) reported that “unhealthy” maternal diet patterns during pregnancy were associated with increased externalizing child behaviors. A recent study in the United Kingdom suggested that maternal diets characterized by higher intakes of fruits and vegetables and lower intakes of meat and potatoes are associated with higher child IQ at age 8 years ( Freitas-Vilela et al, 2017 ). In the Generation R study involving 3,104 children, investigators reported decreased levels of externalizing behaviors from children born to mothers who adhered to a Mediterranean diet during pregnancy, and increased child externalizing behaviors in children born to mothers who consumed a “Traditionally Dutch” diet consisting of high meat intake (processed and unprocessed), margarines and potatoes ( Steenweg-de Graaff et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal nutrition is important for pregnant women as the developing foetus relies on maternal intake of nutrients critical for foetal growth and development [ 1 , 2 ]. The n -3 long chain PUFA (LCPUFA) docosahexaenoic acid (DHA) and the n -6 LCPUFA, arachidonic acid (AA), are required for growth and development of the brain [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…responsible for promoting the neurodevelopment of children, which reinforces the importance of having a healthy lifestyle before pregnancy even begins. 21 Thus, prenatal care is of fundamental importance to encourage, guide and motivate pregnant women by promoting healthy eating habits 22 and by monitoring the health of the mother and the fetus. 21 In a study on the healthy eating index of Brazilian pregnant women, the overall dietary intake of pregnant women was assessed based on three food groups(vegetables, fruits and beans and other protein-rich vegetables), two ratios (red/white meat and polyunsaturated/saturated fat) and five nutrients (fiber, trans fat, calcium, folate and iron) and it was found that most of them lacked dietary intake improvements, thus showing the need to deliver food education at this stage of life.…”
Section: Tablementioning
confidence: 99%
“…21 Thus, prenatal care is of fundamental importance to encourage, guide and motivate pregnant women by promoting healthy eating habits 22 and by monitoring the health of the mother and the fetus. 21 In a study on the healthy eating index of Brazilian pregnant women, the overall dietary intake of pregnant women was assessed based on three food groups(vegetables, fruits and beans and other protein-rich vegetables), two ratios (red/white meat and polyunsaturated/saturated fat) and five nutrients (fiber, trans fat, calcium, folate and iron) and it was found that most of them lacked dietary intake improvements, thus showing the need to deliver food education at this stage of life. 23 In the present study, class III obese and normal weight high-risk pregnant women presented a higher intake of total calories and higher percentages of carbohydrates from ultra-processed foods when compared with overweight and class II obese pregnant women, that is, the consumption of ultraprocessed foods may not be related only to the nutritional status of pregnant women.…”
Section: Tablementioning
confidence: 99%